2010
DOI: 10.1007/s10560-010-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

Examining Gender Differences in Service Utilization among Children: Nature, Nurture, or Social Network?

Abstract: This study builds upon the existing literature by examining gender differences in the service referral and service utilization patterns among children through the lens of biological, social construction, and social networking perspectives. A secondary analysis of county wide data was used that consisted of a sample of 1,408 children aged 1-11 and data from the Adolescent Information Form (AIF) for the source of referral, contributing factors for referral, and service use histories across multiple sectors of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…In univariate analysis, this study also found patterns of referral associated with gender that warrant investigation in a larger study. Other studies have found that boys and girls often manifest different mental health, social and behaviour patterns (Currie et al., ; Maschi, Perez & Gibson, ). However, Maschi et al () suggest that there is the potential for practitioners and other professionals to be predisposed to gender bias in identifying children's problems, including when making a diagnosis and deciding which service to refer to.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In univariate analysis, this study also found patterns of referral associated with gender that warrant investigation in a larger study. Other studies have found that boys and girls often manifest different mental health, social and behaviour patterns (Currie et al., ; Maschi, Perez & Gibson, ). However, Maschi et al () suggest that there is the potential for practitioners and other professionals to be predisposed to gender bias in identifying children's problems, including when making a diagnosis and deciding which service to refer to.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have found that boys and girls often manifest different mental health, social and behaviour patterns (Currie et al., ; Maschi, Perez & Gibson, ). However, Maschi et al () suggest that there is the potential for practitioners and other professionals to be predisposed to gender bias in identifying children's problems, including when making a diagnosis and deciding which service to refer to. In addition, Sund, Larsson, and Wichstrøm () state that while differences in prevalence rates may reflect true rates, they may also be as a result of variation in methods and measures used for assessment of CYP's mental health difficulties.…”
Section: Discussionmentioning
confidence: 96%
“…Parents in a small qualitative study in Ireland expressed the need for support, enhanced knowledge about suicidal behaviour, parenting skills and strategies for managing future self‐harm (Byrne et al ., ). For some families, a suicide attempt will precipitate increased utilization of mental health services (Chan et al ., ), particularly for vulnerable boys (Maschi et al ., ). However, this may conflict with the general developmental trend for the adolescent of increasing autonomy (Wilson et al ., ).…”
Section: Parental Characteristicsmentioning
confidence: 97%